Comparative Transcriptome Analysis Revealing the Potential Mechanism of Low-Temperature Stress in Machilus microcarpa - He, Xinru; Long, Fengying; Li, Yingjie; Xu, Yaowen; Hu, Longsheng; Yao, Tianshu; Huang, Yingying; Hu, Die; Yang, Yujie; Fei, Yongjun (Frontiers in Plant Science, 2022)
Machilus microcarpa is a national rare tree species in China, and possess important ornamental, ecological value. M. macrocarpa can be planted in low temperature areas depends on whether its seedlings can withstand the harm. However, the regulatory mechanism of cold tolerance in M. macrocarpa seedlings were still unclear. In this study, the annual seedlings of M. macrocarpa were subjected to five temperature treatments [25°C (control), 12℃, 5℃, 0℃, and -5℃]. Eight physiological indexes were measured, relative electric conductivity (REC), malondialdehyde content (MDA), chlorophyll (CHL), soluble protein (SP), soluble sugar (SS), superoxide dismutase (SOD), peroxidase (POD), and polyphenol oxidase (PPO). LT50 was -2.8°C of M. macrocarpa. The total chlorophyll content decreased, the relative electric conductivity, the contents of MDA and soluble sugar, the activities of POD, SOD and PPO increased with decreasing temperature. Illumina RNA-sequencing was employed to M. macrocarpa leaves treated at 25℃, and -2.8℃. A total 50 differentially expressed structural genes (DEGs) and 23 differentially expressed transcription factors (TFs) related to cold tolerance in M. macrocarpa. Among these DEGs, the expression level of 13 genes exhibited the highest expression level, including candidate structural genes (SS, GBE1, PGK, gpmI, ALDO and ENO) and transcription factors (MYB and WRKY), which may play key roles in cold tolerance M. macrocarpa. The results provide valuable information for further studies on cold response mechanisms of cold tolerance in M. macrocarpa.